Оскарження наказу про проведення перевірки як спосіб захисту права - Котенко, А. М. (Право, 2020)
У статті проведено аналіз приписів чинного законодавства та практики Верховного суду щодо оскарження платником податків наказу про проведення перевірки як способу захисту прав такого платника. Аргументовано, що правова позиція ВС щодо неможливості оскарження наказу про проведення перевірки самостійно без оскарження ППР – є нелогічною, оскільки така позиція не враховує приписи чинного законодавства, зокрема, ПК України та КАС України. Підкреслено необхідність перегляду аналізованої правової позиції ВС та формування нової практики ВС стосовно оскарження наказу про проведення податкової перевірки. // The article analyzes the provisions of the current legislation and practice of the Supreme Court to appeal against the taxpayer of the order of inspection as a way to protect the rights of such a payer. It is argued that the legal position of SU regarding the impossibility of appealing the order on conducting verification independently without the appeal of the PPR is illogical, since such a position does not take into account the requirements of the current legislation, in particular, PC of Ukraine and CAS of Ukraine. The need to revise the analyzed legal position of the SU and the formation of a new practice of SW in relation to the appeal of the order on conducting tax audits is emphasized.
Keywords: податкові перевірки; наказ про проведення перевірки; оскарження наказу; захист прав платників податків; tax audits; an order for verification; appeal of the order; protection of taxpayers rights